Bringing Policymakers to Science Through Communication: A Perspective From Latin America - Pulido-Salgado, Marta; Castaneda Mena, Fátima Antonethe (Frontiers in Research Metrics and Analytics, 2021)
Scientific knowledge should be shared beyond academic circles in order to promote science in policymaking. Science communication increases the understanding on how natural world works and the capacity to make informed decisions. However, not every researcher has the ability to master the art of communicating, and even less in a clear, concise and easy to understand language that society representatives appreciate. Within the huge and extraordinarily diverse Latin American region science communication has been going on for at least 200 years; when the first science stories appeared in the newspapers, as well as the first science museums and botanical gardens were founded. Nevertheless, resources are limited, and notably time, which researchers spend mostly in mentoring, ensuring funding, publication of their results and laboratory work, while scientific journalists are an endangered species. This perspective article aims at providing some recommendations to build bridges between science and decision-making parties, through communication, by exploring how Latin American diplomats and policymakers engage with scientific knowledge.